Modern Trends in the Development of Content by Managerial Training in Education (Journal of Educational Sciences, 2017)
The article discusses the management training for the organization of education taking into account modern trends in the field of management. These trends are: the emergence of a global “Golden Fund” and to seek ways of methodological updates in the field of management in the context of the development of management theory; the blurring of the boundaries between different scientific directions and schools, the internationalization of knowledge; occurrence in world educational space; change the coordinate system of management of business process; leadership in their field; Informatization management; cooperation and integration into the world educational space; development of management teams; formation and development and human capital; the degree of novelty for the time factor; the inclusion of the practices of organizations and the renewal of education with the requirements of international standards; focus on quality of services/product. Each trend is associated with the development of management concepts and its accounting treatment recommended in the fullness of the disciplines in the educational process of management personnel.
Keywords: management of education; current trends in management; education managers; management training